bài 1 : tính
3 + 3 =
6 + 6 =
9 + 9 =
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{3}{5}+\dfrac{4}{3}\times\dfrac{5}{6}=\dfrac{3}{5}+\dfrac{10}{9}=\dfrac{27}{45}+\dfrac{50}{45}=\dfrac{77}{45}\)
\(2-\dfrac{7}{6}+\dfrac{1}{3}=\dfrac{12}{6}-\dfrac{7}{6}+\dfrac{2}{6}=\dfrac{7}{6}\)
\(\dfrac{7}{6}\times3-\dfrac{3}{5}=\dfrac{7}{2}-\dfrac{3}{5}=\dfrac{35}{10}-\dfrac{6}{10}=\dfrac{29}{10}\)
3 + 1 + 6 = 4 + 6 = 10
8 – 4 – 3 = 4 – 3 = 1
9 – 1 – 3 = 8 – 3 = 5
3 + 4 + 2 = 7 + 2 = 9
\(\dfrac{3}{5}+\dfrac{9}{35}=\dfrac{21}{35}+\dfrac{9}{35}=\dfrac{30}{35}\)\(=\dfrac{6}{7}\)
\(\dfrac{3}{4}\times\dfrac{5}{7}=\dfrac{15}{28};\dfrac{5}{8}\times\dfrac{4}{15}=\dfrac{20}{120}=\dfrac{1}{6};\dfrac{7}{12}\times\dfrac{4}{9}=\dfrac{28}{108}=\dfrac{7}{27};\)
\(\dfrac{1}{6}\times\dfrac{3}{5}=\dfrac{3}{30}=\dfrac{1}{10};\dfrac{12}{21}\times\dfrac{23}{8}=\dfrac{276}{168}=\dfrac{23}{14};\dfrac{13}{4}\times\dfrac{5}{39}=\dfrac{65}{156}=\dfrac{5}{12}\)
\(\dfrac{7}{42}\times\dfrac{13}{21}=\dfrac{91}{882}=\dfrac{13}{126};\dfrac{3}{16}\times\dfrac{4}{15}=\dfrac{12}{240}=\dfrac{1}{20}\)
`5`
`a, -7/21 +(1+1/3)`
`=-7/21 + ( 3/3 + 1/3)`
`=-7/21+ 4/3`
`=-7/21+ 28/21`
`= 21/21`
`=1`
`b, 2/15 + ( 5/9 + (-6)/9)`
`= 2/15 + (-1/9)`
`= 1/45`
`c, (9-1/5+3/12) +(-3/4)`
`= ( 45/5-1/5 + 3/12)+(-3/4)`
`= ( 44/5 + 3/12)+(-3/4)`
`= 9,05 +(-0,75)`
`=8,3`
`6`
`x+7/8 =13/12`
`=>x= 13/12 -7/8`
`=>x=5/24`
`-------`
`-(-6)/12 -x=9/48`
`=> 6/12 -x=9/48`
`=>x= 6/12-9/48`
`=>x=5/16`
`---------`
`x+4/6 =5/25 -(-7)/15`
`=>x+4/6 =1/5 + 7/15`
`=> x+ 4/6=10/15`
`=>x=10/15 -4/6`
`=>x=0`
`----------`
`x+4/5 = 6/20 -(-7)/3`
`=>x+4/5 = 6/20 +7/3`
`=>x+4/5 = 79/30`
`=>x=79/30 -4/5`
`=>x= 79/30-24/30`
`=>x= 55/30`
`=>x= 11/6`
\(5)\)
\(A=\dfrac{-7}{21}+\left(1+\dfrac{1}{3}\right)\)
\(A=\dfrac{-7}{21}+\dfrac{4}{3}\)
\(A=\dfrac{-7}{21}+\dfrac{28}{21}\)
\(A=1\)
\(--------------\)
\(B=\dfrac{2}{15}+\left(\dfrac{5}{9}+\dfrac{-6}{9}\right)\)
\(B=\dfrac{2}{15}+\dfrac{-1}{9}\)
\(B=\dfrac{18}{135}+\dfrac{-15}{135}\)
\(B=\dfrac{1}{45}\)
\(------------\)
\(C=9-\dfrac{1}{5}+\dfrac{3}{12}+\dfrac{-3}{4}\)
\(C=\dfrac{44}{5}+\dfrac{3}{12}+\dfrac{-3}{4}\)
\(C=\dfrac{528}{60}+\dfrac{15}{60}+\dfrac{-3}{4}\)
\(C=\dfrac{181}{20}+\dfrac{-3}{4}\)
\(C=\dfrac{181}{20}+\dfrac{-15}{20}\)
\(C=\dfrac{83}{10}\)
\(6)\)
\(a)\) \(x+\dfrac{7}{8}=\dfrac{13}{12}\)
\(x=\dfrac{13}{12}-\dfrac{7}{8}\)
\(x=\dfrac{104}{96}-\dfrac{84}{96}\)
\(x=\dfrac{5}{24}\)
\(b)\) \(\dfrac{-6}{12}-x=\dfrac{9}{48}\)
\(\dfrac{-1}{2}-x=\dfrac{3}{16}\)
\(x=\dfrac{-1}{2}-\dfrac{3}{16}\)
\(x=\dfrac{-8}{16}-\dfrac{3}{16}\)
\(x=\dfrac{-11}{16}\)
\(c)\) \(x+\dfrac{4}{6}=\dfrac{5}{25}-\left(-\dfrac{7}{15}\right)\)
\(x+\dfrac{4}{6}=\dfrac{5}{25}+\dfrac{7}{15}\)
\(x+\dfrac{4}{6}=\dfrac{75}{375}+\dfrac{105}{375}\)
\(x+\dfrac{4}{6}=\dfrac{12}{25}\)
\(x=\dfrac{12}{25}-\dfrac{4}{6}\)
\(x=\dfrac{72}{150}-\dfrac{100}{150}\)
\(x=\dfrac{-14}{75}\)
\(d)\) \(x+\dfrac{4}{5}=\dfrac{6}{20}-\left(-\dfrac{7}{3}\right)\)
\(x+\dfrac{4}{5}=\dfrac{6}{20}+\dfrac{7}{3}\)
\(x+\dfrac{4}{5}=\dfrac{18}{60}+\dfrac{140}{60}\)
\(x+\dfrac{4}{5}=\dfrac{79}{30}\)
\(x=\dfrac{79}{30}-\dfrac{4}{5}\)
\(x=\dfrac{79}{30}-\dfrac{24}{30}\)
\(x=\dfrac{11}{6}\)
1: =1/8*9/4=9/32
2: =8/27*243/32=9/4
3: =(5/4*4/5)^5*(4/5)^2=16/25
4: \(=\left(-\dfrac{5}{6}\cdot\dfrac{6}{5}\right)^2\cdot\left(\dfrac{6}{5}\right)^2=\dfrac{36}{25}\)
5: \(=\left(-\dfrac{4}{3}\right)^3\cdot\left(\dfrac{3}{4}\right)^{10}=\left(-1\right)\left(\dfrac{3}{4}\right)^7=-\left(\dfrac{3}{4}\right)^7\)
6: \(=\left(\dfrac{1}{3}\cdot\dfrac{-9}{2}\right)^4\left(-\dfrac{9}{2}\right)^2=\left(-\dfrac{3}{2}\right)^4\cdot\dfrac{81}{4}=\dfrac{9}{4}\cdot\dfrac{81}{4}=\dfrac{729}{16}\)
8: =(0,2*5)^4*5^2=25
10: =-0,5^5*2^10
=-0,5^5*2^5*2^5
=-32
13: =(0,5*2)^2*2^2=4
bài 1 : 1 + 3 + 5 + 7 + 9 + 10 + 8 + 6 +4 +2 + 0
= ( 1+ 9 ) + ( 2 + 8 ) + ( 3 + 7 ) + ( 4 + 6 ) + 5 + ( 10 + 0 )
= 10 x 5 + 5
= 55
baì 2 : 10 - 9 + 8 - 7 + 6 - 5 + 4 - 3 + 2 -1
= 1 + 1 +1 +1 +1
= 5
3 + 3 = 6
6 + 6 = 12
9 + 9 = 18
3 + 3 = 6
6 + 6 = 12
9 +9= 18